What Constitutes The Elements Of A Nursing Continence Assesment: A Literature Review - Made Sumawarti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2001)
Urinary incontinence is a treatable condition. It, however, is a possible to tackle incontinence before finding the cause of this problem. The cause of incontinence may be established through an accurate assessment. As the first phase in the process of nursing care, assessment takes a key position to successful outcome. The comprehensive assessment includes questions about history, medication review, a bladder/voiding diary, environmental assessment, physical examination, functional assessment, and additional test such as urinalysis, culture, post void residual measurement, and urodynamic.Â Inkontinensia urine merupakan kondisi ang dapat ditangani. Penanganan inkontinesia urin ini hanya dapat ditangani secara tepat apabila penyebabnya diketahui terlebih dahulu. Penyebab ini dapat diketahui melalui pengkajian. Sebagai tahap awal dari asuhan keperawatan, pengkajian merupakn kunci eberhasilan dari tindakan yang akan dilakukan. Pengkajian untuk inkontinensia urin ini melipui riwayat kesehatan yang lalu, riwayat medis, catatn harian pemasukan dan pengeluaran cairan, pengkajian lingkungan, pengkajian fisik dan fungsi. Pengkajian yang lain meliputi urinalisi, kultur urin, tes residu urin dan urodinamika.